Exploring the Influence of Innovation Characteristics on the Adoption of a Water and Input Saving Technology in the Jordan Valley: Implications for Community Extension Workers - Mary T. Rodriguez; T. Grady Roberts; Amy Harder (Journal of International Agricultural and Extension Education, 2018)
As the world’s population is set to increase to an estimated 9.6 billion people, the greater the strain becomes on the food system to meet people’s food and nutrition needs (United Nations, 2013). The MENA region is expected to increase in population by double by 2050 further straining their water and food resources (IFPRI, 2010). Improved innovations to increase production have been encouraged to address those issues. Fertigation, and in particular the more effective hydraulic injector, was introduced in the Jordan Valley to help manage the amount of fertilizer application, reduce run-off in irrigated agriculture, and improve water use efficiency. However, despite its advantages, the hydraulic injector fertigation technology has not been widely adopted. This study sought to better understand this phenomena through the use of mixed methods research on the impact of innovation characteristics, as defined by Rogers (2003), on adoption of the technology. Results found complexity to have a statistically significant impact on adoption and to be a significant predictor of adoption. While not specifically a component of Roger’s innovation characteristics, affordability was a key factor in non-adoption.
Keywords: Jordan; adoption; fertigation; Diffusion of Innovations